Axiotherapy of Non-Accountable Perpetrators of Criminal Acts - Grzegorz Kudlak (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Axiotherapy is an original project built on value-based therapy carried out in a forensic psychiatry ward. It is addressed to persons who committed a criminal act and were deemed by the court to be non-accountable or of limited accountability at the time of the crime. As a result, they were referred for treatment as part of the imposed preventive measures. Patients treated at the forensic psychiatry ward are most often perpetrators of violent crimes. While suffering from various mental disorders, they also exhibit impulsive behaviour leading to criminal acts. Such behaviour has far-reaching consequences for both the patient and the general public. Mental disorders of forensic psychiatry patients, the course of the disease, the degree of aggression and associated circumstances (such as addiction, sexual preferences disorders, and personality disorders) indicate a crisis in the sphere of values, which could be one of the factors leading to the serious crime. Working with a value system that determines a person's behaviour means working on a system that motivates and activates them and can change over time. Axiotherapy is intended to help patients to work out their value system and to identify their transcendentals, as appropriate.